The correlation between environmenta determinants and employee health protocol behavior with symptoms of covid-19 exposure in laboratory companies - Nurhidayanto, Dede; Dewi, Yusriani Sapta (Fakultas Teknik - Universitas Satya Negara Indonesia, 2025)
This study aims to determine the correlation between environmental determinants and health protocol behavior with symptoms of Covid-19 exposure. The research method used was survey with a quantitative approach. The data were analyzed using correlation and multiple linear regression. The research was conducted at Laboratory Companies, South Jakarta, from November to January 2024. The sampling technique used. This study aims to determine the correlation between environmental determinants and health protocol behavior with symptoms of Covid-19 exposure. The research method used was survey with a quantitative approach. The data were analyzed using correlation and multiple linear regression. The research was conducted at Laboratory Companies, South Jakarta, from November to January 2024. The sampling technique used was simple random sampling, and the sample size was 31 employees working at Laboratory Companies, in South Jakarta. The results of a regression analysis was the formula of Y = 36.979 - 0.321X1 - 0.181X2. The results of the significance and linearity test were Fcount 15.92 > Ftable 4.04 at α = 0.05. The correlation coefficient between the physical office environment and employee health protocol behavior with symptoms of Covid-19 exposure was 0.729, R = 0.53, meaning that the relationship between X1 + X2 and Y is 53%. The results of the study showed that there was a negative and significant relationship between the physical office environment and employee health protocol behavior with symptoms of exposure to Covid-19. was simple random sampling, and the sample size was 31 employees working at Laboratory Companies, in South Jakarta. The results of a regression analysis was the formula of Y = 36.979 - 0.321X1 - 0.181X2. The results of the significance and linearity test were Fcount 15.92 > Ftable 4.04 at α = 0.05. The correlation coefficient between the physical office environment and employee health protocol behavior with symptoms of Covid-19 exposure was 0.729, R = 0.53, meaning that the relationship between X1 + X2 and Y is 53%. The results of the study showed that there was a negative and significant relationship between the physical office environment and employee health protocol behavior with symptoms of exposure to Covid-19.